Feminist Ethics and Research with Women in Prison - Quinlan, Christina (The prison journal, 2022)
In this article, a new model, An Ethic of Empathy, is proposed as a guide for researchers, particularly new scholars to the discipline. This model emerged from the authors’ concerns regarding the application of ethics to studies that focus on the experience of female offenders in criminal justice systems. The key issue is the vulnerability of incarcerated and post-release women in relationship to the powerful status of social scientist researchers. The complexity of ethics in such research settings necessitates a particular ethical preparation, involving formation, reflection, understanding, commitment, care, and empathy. Three cases are outlined which document the authors’ ethical formations as researchers.